Rancang Bangun Aplikasi Pengelolaan Arsip Surat Pada Kantor Kepala Desa Cikaduwetan Menggunakan PHP & MySQL - Dadan Nugraha; Asih Awalia (Universitas Kuningan, 2018)
Cikaduwetan Headman Office is a institude assisted by several staff as element of village government, but one of staffs in Secretariat especially Kaur Umum has a problem in managing letter archives manually by archived incoming letter and outgoing letter by writing in master book so the letter archive can easily pile up, lost, and broke, and then searching for archieve letter takes a long time because they have to search one by one, and there is no disposition format. By analyzing problem indication, writer can make conclusion that it is the opportunity for developing Letter Archive Management Application Using PHP and MySQL which is applied At Cikaduwetan Headman. PHP is a programming language that is usually used for development application and MySQL is a database used for saving letter data. So by using Letter Archive Management Application can help and facilitate Cikaduwetan Secretariat especially Kaur Umum in managing letter archives that have to be computerized and well structured. Keywords: Letter, Archive, Application, PHP, MySQL.